Pengaruh Net Profit Margin, Earning per Share, dan Leverage terhadap Kebijakan Dividen (Studi Empiris pada Perusahaan Indeks High Dividend 20 yang Terdaftar di Bursa Efek Indonesia Tahun 2018–2022) - Mutiara, Wawa (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2025)
This study aims to examine and analyze the effects of Net Profit Margin, Earning Per Share, and leverage on dividend policy in companies included in the High Dividend 20 Index and listed on the Indonesia Stock Exchange during the 2018–2022 period. This research employs an associative quantitative approach using secondary data obtained from company financial reports. The sample was selected using purposive sampling and consisted of 12 companies from a population of 29 High Dividend 20 Index companies, resulting in 60 firm-year observations. Data were analyzed using multiple linear regression with SPSS version 26. The results show that Net Profit Margin has a negative and significant effect on dividend policy. Meanwhile, Earning Per Share and leverage do not have significant effects on dividend policy. Simultaneously, Net Profit Margin, Earning Per Share, and leverage affect dividend policy. The adjusted coefficient of determination is 14.4%, indicating that the three independent variables explain 14.4% of the variation in dividend policy, while the remaining variation is explained by other factors outside the research model.